Integrative anatomical study of the branched annelid Ramisyllis multicaudata (Annelida, Syllidae). (12th April 2021) - Ponz‐Segrelles, Guillermo; Glasby, Christopher J.; Helm, Conrad; Beckers, Patrick; Hammel, Jörg U.; Ribeiro, Rannyele P.; Aguado, M. Teresa
Abstract: The sponge‐dwelling Syllidae Ramisyllis multicaudata and Syllis ramosa are the only annelid species for which a branched body with one head and multiple posterior ends is known. In these species, the head is located deep within the sponge, and the branches extend through the canal system of their host. The morphology of these creatures has captivated annelid biologists since they were first discovered in the late XIXth century, and their external characteristics have been well documented. However, how their branched bodies fit within their symbiotic host sponges and how branches translate into internal anatomy has not been documented before. These features are crucially relevant for understanding the body of these animals, and therefore, the aim of this study was to investigate these aspects. In order to assess these questions, live observation, as wells as histology, immunohistochemistry, micro‐computed tomography, and transmission electron microscopy techniques were used on specimens of R . multicaudata . By using these techniques, we show that the complex body of R . multicaudata specimens extends greatly through the canal system of their host sponges. We demonstrate that iterative external bifurcation of the body is accompanied by the bifurcation of the longitudinal organ systems that are characteristic of annelids. Additionally, we also highlight that the bifurcation process leaves an unmistakable fingerprint in the form of newly‐described "muscle bridges." These structures theoretically allow one to distinguish original and derived branches at each bifurcation. Last, we characterize some of the internal anatomical features of the stolons (reproductive units) of R . multicaudata, particularly their nervous system. Here, we provide the first study of the internal anatomy of a branched annelid. This information is not only crucial to deepen our understanding of these animals and their biology, but it will also be key to inform future studies that try to explain how this morphology evolved. Abstract :